Application of Artificial Intelligence in Engineering: A Comprehensive Review - Valluri Daneesha (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Artificial intelligence (AI) is changing engineering due to automating complex procedures, refining the design optimization, enhancing decision-making, and implementing predictive maintenance. This paper summarizes state of the art application of AI to several different disciplines of engineering such as civil, mechanical, electrical, and computer engineering. From the review, one can see the merging of machine learning, deep learning, computer vision, and natural language processing into solving traditional engineering problems. Important developments, tools, frameworks, and implementations into real life cases are analyzed to reveal what is trendy nowadays and what can be projected in the future. The research comes to a conclusion that AI does not only enhance efficiency and precision in engineering processes, but it also spurs innovation by means of intelligent automation and data insights.